2015
DOI: 10.3109/09638288.2015.1061605
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating employment opportunities for adults with intellectual and developmental disability through parents and social networks

Abstract: Practitioners must understand how to support parents to be effective advocates for their adult children with IDD, assist them to develop and maintain their social networks and help them to avoid caregiver burnout. Implications for Rehabilitation People with intellectual and developmental disability (IDD) face numerous challenges in indentifying work options and overcoming barriers to employment. Parents and other non-paid support members of social networks can be instrumental in ensuring that persons with IDD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 24 publications
3
46
0
2
Order By: Relevance
“…108–446). At later ages as well, parent-family contacts and social networks seem instrumental in helping adults with disabilities acquire both employment (Petner-Arrey, Howell-Moneta, & Lysaght, 2015) and informal supports (Sanderson, Burke, Urbano, Arnold, & Hodapp, in press). Summarizing the role of parents during the transition and early-adult years, Timmons et al (2004) concluded that parents serve as the linchpin for services, holding together as a single unit the complex service systems that assist young adults with disabilities.…”
mentioning
confidence: 99%
“…108–446). At later ages as well, parent-family contacts and social networks seem instrumental in helping adults with disabilities acquire both employment (Petner-Arrey, Howell-Moneta, & Lysaght, 2015) and informal supports (Sanderson, Burke, Urbano, Arnold, & Hodapp, in press). Summarizing the role of parents during the transition and early-adult years, Timmons et al (2004) concluded that parents serve as the linchpin for services, holding together as a single unit the complex service systems that assist young adults with disabilities.…”
mentioning
confidence: 99%
“…We thought that this discovering and hypothesis-generating method would be very appropriate for fathoming the social participation of people with disabilities in various areas of life as openly and as in depth as possible and for elaborating the concepts and dimensions found empirically in the best possible way. As demonstrated in other grounded theory studies, this methodology can produce highly relevant and innovative research outcomes for policy and practice, especially when it comes to underexplored and socially marginalized or excluded population groups [14,[20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…What this means in daily life for persons with impairments and how participation (restriction) is experienced subjectively in this area has not yet been explored sufficiently in current research. The importance of the family of origin and social networks for participation in other areas of life (e.g., work) has been documented scientifically [14,18]. In a Canadian sample using a grounded theory approach, Petner-Arrey et al…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is problematic as it is increasingly apparent that job seekers with disabilities have Job Seekers with Disabilities 83 a distinct experience. For example, recent studies illustrate how job seekers with disabilities use unique job search pathways offered by government disability employment agencies (Kulkarni and Scullion, 2015), rely on qualitatively different personal networks (Dimakos et al, 2016;Langford, Lengnick-Hall and Kulkarni, 2013;Petner-Arrey, Howell-Moneta and Lysaght, 2016) and face distinct social expectations about their abilities (Baldridge and Kulkarni, 2017;Jammaers, Zanoni and Hardonk, 2016). Despite this growing interest, the process by which job seekers move from initial dispositional states to employment offers, and the roles of employment agencies, family and disability type in that process, are yet to be fully elaborated.…”
mentioning
confidence: 99%